PEMBELAJARAN KOLABORATIF BERSAMA PRAKTISI BIDANG PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN (B3) DALAM MENGIMPLEMENTASIKAN PERMENLHK NO. 6 TAHUN 2021 - Maziya, Fina Binazir (Refleksi Pembelajaran Inovatif, 2024)
Collaborative learning with practitioners is an effort to enhance the learning atmosphere in the classroom, helping students better understand and explore materials that predominantly apply regulations in Indonesia. The practitioners involved are alumni of the Environmental Engineering Study Program, who have an emotional connection with the students, fostering a sense of familiarity and comfortable communication. These practitioners provide insights and reinforcement of materials related to hazardous and toxic waste (B3) management systems in the industrial sector, particularly in the areas of their expertise. Students are assigned case studies to prepare environmental documents related to B3 waste management in the industrial field. They engage in mentoring sessions with practitioners to facilitate a "knowledge transfer" process. The outcomes of this collaborative activity reveal several benefits, including students’ increased confidence in asking questions and engaging in discussions with practitioners, the emergence of critical thinking, and the development of effective problem-solving skills when completing assignments and addressing challenges collaboratively. In terms of document completeness, 80% of the students successfully met the requirements for environmental documents in compliance with applicable regulations. One challenge faced during the course was the occasional scheduling conflict caused by emergency conditions encountered by practitioners at their workplaces. However, overall, the students demonstrated their ability to understand and apply the regulations in Indonesia, particularly in preparing the Technical Details Document for B3 Waste Storage in the industrial sector, as stipulated by the Minister of Environment and Forestry Regulation Number 6 of 2021 on Procedures and Requirements for Hazardous and Toxic Waste Management.